Pengaruh Debt to Equity Ratio, Return on Assets, Ukuran Perusahaan, dan Current Ratio terhadap Nilai Perusahaan Sektor Consumer Goods yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021 - Kumba Digdowiseso; Yuli Rianasari (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The purpose of this study is to produce the latest empirical evidence regarding the effect of Debt to Equity Ratio (DER), Return on Assets (ROA), Firm Size, and Current Ratio (CR) on Firm Value in Consumer Goods Sector listed on the Indonesia Stock Exchange for the period 2017-2021. This research was made because there are still differences in research results between one another and the fluctuations in the firm value in the consumer goods sector companies listed on the Indonesia Stock Exchange. The study was conducted on 41 samples of companies using purposive sampling in the 2017-2021 period. The data analysis method uses panel data regression method which is processed using statistical software STATA 17. The results of the study show empirical evidence that the Debt to Equity Ratio variable has a positive and insignificant effect on firm value. The Return on Assets and Firm Size variable has a positive and significant effect on firm value. The Current Ratio variable has a negative and insignificant effect on firm value. Keywords: Debt to Equity Ratio (DER), Return On Assets (ROA), Firm Size, Current Ratio (CR), and Firm Value